Evaluation of stress urinary incontinence in physically active and childlessPolish females: a cross-sectional study - Kopyra, Katarzyna; Chomiuk, Tomasz; Kasiak, Przemysław; Mamcarz, Artur; Śliż, Daniel (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Stress urinary incontinence (SUI) is a global health problem. The popularity of physical activity is increasing, andSUI affects more individuals, primarily young, physically active females. The aims of the study were to (I) determine the relationship between the type of physical activity and the frequency of SUI in females and (II) assess the treatment methods used forSUI by females.Methods. The study was conducted using a 20-point questionnaire among females. The inclusion criteria were (I) childlessness,(II) physical activity > 2 times/week, and (III) a history of SUI. The questions were related to (I) socio-demographic characteristics,(II) type and description of physical activity, and (III) frequency of SUI and used treatment.Results. Seventy-three females (aged 18–35 years) fulfilled the inclusion criteria. Thirty-four (46.6%) trained in endurance sports,32 (43.8%) practiced strength training, and 7 (9.6%) preferred yoga. Most females had 2–3 weekly training sessions (n = 51,69.9%). Seventy-one (97.2%) did not use any form of treatment for SUI. Females more often suffered from SUI during training thanin everyday activities (p = 0.003), and this relationship was more frequently noticed during longer workouts (p = 0.02). There wereno significant relationships between SUI and preferred sports discipline (p = 0.38), number of practiced sports disciplines (p = 0.22),training experience (p = 0.21), or weekly training volume (p = 0.24).Conclusions. The frequency of SUI depends on the type and amount of physical activity. Females mostly do not use treatmentfor SUI. Physicians and physiotherapists should consider the type and level of patients’ physical activity when diagnosing SUIand prescribing treatment.
Keywords: stress urinary incontinence; females; sports; physical activity; training